PELAKSANAAN TANGGUNG JAWAB SOSIAL DAN LINGKUNGAN PADA PT. FREEPORT INDONESIA SEBAGAI PT. PENANAM MODAL DALAM RANGKA PERLINDUNGAN DAN PENGELOLAAN LINGKUNGAN HIDUP (Jurnal Hukum Mimbar Justitia, 2018)
Implementation of social and Environmental Responsibility is the obligation of the company that should be budgeted and accounted for as expenses the company conducted with attention to propriety and obligation. Program of social responsibility and the environment must be included in the annual work plan and budget a limited liability company according to Law Number 40 of the year 2007 On limited liability company and Act No. 25 of the year 2007. The problem how form the implementation of social and Environmental Responsibility at the PT. Freeport Indonesia as PT. Planter foreign capital in mining?, and whether Act No. 40 Year 2007 On limited liability company and Act No. 25 of the year 2007 to give legal certainty to the implementation of social and Environmental Responsibility (TJSL) on PT. Freeport Indonesia?. The method of the approach used in this study using normative juridical approach, with the main focus is the implementation of TJSL on PT. Freeport Indonesia with the data acquired and analyzed using the methods of normative qualitative. Results of the study showed a real form of legal certainty is the implementation or enforcement of the law against an act regardless of who is doing. With the certainty of the law. and Act No. 40 Year 2007 On limited liability company and Act No. 25-year 2007 has not been able to guarantee the legal certainty of implementation of TJSL/CSR. Because of the vagueness in the substance of its settings. Keywords: Protection, Management, Environment.